Vietnam :water resources sector review - main report /World Bank, Asian Development Bank, FAO & UNDP. - World Bank, Asian Development Bank, FAO & UNDP.
A report by the World Bank, FAO, UNDP and the NGO Water Resources Group in cooperation with the Institute of Water Resources Planning, Vietnam